Shaping Entrepreneurial Design Identity in Design Education - Beate Cesinger; Sandra Dittenberger (She Ji: The Journal of Design, Economics and Innovation)
This article employs social identity theory and findings from research on design identity, entrepreneurial identity, and entrepreneurship education to discuss transdisciplinary design education at the intersection of design and entrepreneurship, which aims to foster an entrepreneurial design identity. As a professional group, designers share values and norms about their work and practice. In contrast, entrepreneurial identity is broader, with the market as its primary reference point. This distinction results in a distance between entrepreneurial identity and professional identity, making designers’ professional careers more challenging, limiting entrepreneurial intention, and reducing the chances of survival of design ventures. To address this, we first delineate the theoretical foundation of entrepreneurial identity and design identity and discuss their current coexistence. We then offer suggestions on how to bridge the gap between the two identities to foster an entrepreneurial design identity in design education. The article concludes with a research agenda and preliminary practical recommendations to lay the ground for integrating the two identities and developing an entrepreneurial design identity.